Peran Manajemen Waktu dan Kedisiplinan Dalam Mempengaruhi Hasil Belajar Optimal (Equilibrium: Jurnal Pendidikan, 2021)
This study aims to analyze the role of time management and discipline on optimal learning outcomes. This research is a survey research with a population of junior high school and senior high school students of the Islamic Education Foundation Nur el Arafah Bekasi. The sample was taken by random sampling technique of 85 people. The instrument used was a questionnaire. Data analysis using multiple regression. From data processing, the results obtained: 1). There is a significant effect of time management and discipline together on optimal learning outcomes as evidenced by the results of the value of Fh = 24.324 and Sig. = 0.000
Keywords: Time management; Discipline and Optimal Learning Outcomes